Market Development Strategies for Sustainable Business Growth in Refillable Drinking Water Depot - Septiana, Nabila; Prameka, Adelia Shabrina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to analyze the current business conditions of Sumber Bening, a drinking water refill business, and to develop strategic business planning recommendations to overcome operational challenges and support sustainable business development. Design/Methodology/Approach – This study employs a qualitative descriptive research approach. Data were collected through interviews, observations, and documentation. An in-depth analysis of the current business conditions was conducted as the basis for formulating a comprehensive business plan and identifying strategic actions for business improvement. Findings – The results indicate several strategic initiatives that can be implemented by Sumber Bening to improve business performance, including adding logo stickers to product packaging, extending operational hours, providing additional operational equipment, improving production processes, utilizing social media for promotion, expanding delivery areas, enhancing human resource capabilities, and strengthening financial management practices. These strategies are expected to improve operational effectiveness, market reach, and business sustainability. Originality/Value This research is original in developing a structured business plan for a local drinking water refill enterprise based on real operational conditions. The findings provide practical value by offering actionable strategies that can directly support business development and competitiveness.